Teologi Baptisan Kudus Dalam Pengakuan Iman Westminster [The Theology of Holy Baptism in the Westminster Confession of Faith] - Syos Ambarwati; Silpia Silpia; Ridwanta Manogu (Diligentia: Journal of Theology and Christian Education, 2020)
The sacrament of holy baptism is one of the sacraments recognized and accepted in the church. Holy baptism is carried out using water as an element that symbolizes the cleansing or washing of human sins. The Westminster Confession explains that holy baptism is a seal and a sign of the cleansing of believers. Holy baptism can be performed by believing adults as well as children with the beliefs of their parents. Valid holy baptism is in the name of God the Father, the Son and the Holy Spirit. In fact, there are some churches that have always considered holy baptism as an instrument of salvation and truly the water of baptism cleanses the sins of mankind. In addition, some churches also reject the baptism of children and baptism is believed to be done repeatedly for personal and church reasons. The truth held as the cleansing of sins is only the blood of Christ shed on the cross, baptism is only a stamp and a sign. The purpose of writing this paper is to explain theologically holy baptism in Wesminster's creed. The method of writing this paper is a literature review.